INTESTINAL MICROBIOTA AND NEUROINFLAMMATION IN ADULTS: A review of the gut-mind-body connection (REMUNOM, 2026)
The connection between the gut microbiota and mental health has been widely discussed in the scientific literature, especially in the context of neuropsychiatric and inflammatory disorders. This study aims to gather evidence on how gut microbiota imbalance (dysbiosis) influences the manifestation of neuropsychiatric and inflammatory symptoms in adults, with an emphasis on the gut-mind-body connection. This is a descriptive, qualitative, integrative literature review conducted between 2020 and 2024, using the LILAC, MEDLINE, and PUBMED databases. Sixteen studies were included, indicating that interventions with probiotics, synbiotics, and fecal microbiota transplantation (FMT) showed significant effects in reducing symptoms such as anxiety, depression, and cognitive impairment, although FMT has limited evidence in humans. Mechanisms such as increased intestinal permeability, HPA axis activation, reduced SCFAs, and modulation of pro-inflammatory cytokines stand out. Although the results are promising, methodological gaps persist regarding strain standardization, dosages, and clinical scales. The conclusion is that microbiota modulation represents a promising therapeutic approach, but larger-scale trials with methodological rigor are still needed to consolidate the evidence.